A Bibliometric Review of Signaling Theory in Sustainability Research - Sayuti, Alfian; Muliani; Lestari, Ayu Ambang; Aryani, R. Ayu Ida (Universitas Pamulang, 2026)
This study provides a comprehensive bibliometric review of how signaling theory has been applied in sustainability research during the period 2015–2025. Although signaling theory has been widely used to explain how firms reduce information asymmetry through sustainability communication, its rapid expansion has led to conceptual fragmentation. To address this issue, the study analyzes Scopus-indexed publications using VOSviewer to map scientific production, influential authors, collaborative networks, co-citation patterns, and keyword clusters. The results show a significant growth of sustainability-related signaling studies, with strong contributions from the United States, China, and several European countries, reflecting a globally interconnected research landscape. Citation networks highlight foundational works on sustainability reporting, legitimacy, greenwashing, and environmental performance as core theoretical anchors. Keyword co-occurrence analysis reveals that signaling theory is increasingly integrated with themes such as ESG disclosure, CSR, corporate governance, environmental values, consumer behavior, and green innovation, indicating a broad and interdisciplinary application of sustainability signals. However, the findings also show persistent inconsistencies in how signals are conceptualized, particularly regarding the credibility and authenticity of sustainability disclosures. Overall, this study offers an updated intellectual mapping of the field, clarifies dominant theoretical patterns, and identifies conceptual gaps. Future research is encouraged to strengthen theoretical integration, expand focus on emerging markets, and explore new forms of digital and AI-driven sustainability signaling.